Mesoporous zinc platinate and platinum nanotubes: insights into the formation mechanism and their catalytic activity. Issue 20 (15th August 2022) - Shetty, Shwetha; Mathur, Ankita; Sakhuja, Neha; Chatterjee, Dipanwita; Kundu, Subhajit; Halder, Aditi; Bhat, Navakanta; Ravishankar, N.
Abstract : Mesoporous nanotubes with their 1D morphology, high surface area, and numerous active sites have a distinct microstructural advantage over ultrafine nanoparticles resulting in improved performance over ultrafine nanoparticles. Abstract : Mesoporous nanostructures with their unique morphology, high accessible surface area, and numerous active sites have a distinct microstructural advantage over ultrafine nanoparticles. To incorporate hierarchical porosity, sacrificial template-based approaches are beneficial as they have the advantage of efficient rendering of morphology and simultaneous removal of the template material. It is also crucial to study the behavior of the template material and its reactivity with the deposited material under the reaction conditions. Herein, we have proposed an ultrafast microwave technique to synthesize mesoporous nanotubes of a novel phase zinc platinate (Zn2 PtO4 ) using ZnO as a sacrificial template. We have observed that under the ultrafast kinetics offered by the microwave, aided with reaction temperature, the core ZnO reacts with the adhering hydrolyzed Pt precursor complex to form a mesoporous zinc platinate shell. By designing control experiments, we have attributed the mechanism of formation to a modified sacrificial template-assisted hydrolysis (STAH) process. The controlled, simple reduction step of Zn2 PtO4 nanotubes using NaBH4 results in the formation of mesoporous Pt nanotubes. The mesoporous nature of Zn2 PtO4 nanotubes and enhanced surface area (54 m 2 g −1 ) aids in highly sensitive (down to 300 ppb) and selective sulphur dioxide (SO2 ) detection at room temperature. The mesoporous Pt nanotubes show exceptional catalytic activity towards the methanol oxidation reaction (MOR) and oxygen reduction reaction (ORR) which is attributed to their unique morphology. This synthesis strategy offers a unique approach to designing mesoporous structures of other zinc-based mixed metal oxides and conveniently converting them to their active metal counterparts.